2011
DOI: 10.1071/mf10222
|View full text |Cite
|
Sign up to set email alerts
|

Comparing food-web impacts of a native invertebrate and an invasive fish as predators in small floodplain wetlands

Abstract: Gambusia holbrooki is an invasive predatory poeciliid fish in wetlands of south-eastern Australia, where it coexists with the native waterbug Anisops thienemanni (Notonectidae). Gambusia has been shown to produce trophic cascades, leading to increased algal biomass following invasion, whereas these effects relative to the often-dominant invertebrate predator Anisops are unknown. Given its flexible diet, we predicted that Gambusia would feed more broadly than Anisops, thereby reducing the abundance of zooplankt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…2a–d, 3). Poeciliids are known to drive such cascades in more diverse systems (Hurlbert et al 1972, Nagdali and Gupta 2002, Ho et al 2011), but our study describes a trophic cascade whereby poeciliids alter entire pond ecosystems by reducing the abundance and feeding of a single species, H. rubra . The relative lack of other species of invertebrate grazers in this system, and, specifically, the lack of any species resistant to poeciliid predation, prevents compensation by other members of the community from offsetting the effects of reduced H. rubra grazing.…”
Section: Discussionmentioning
confidence: 94%
“…2a–d, 3). Poeciliids are known to drive such cascades in more diverse systems (Hurlbert et al 1972, Nagdali and Gupta 2002, Ho et al 2011), but our study describes a trophic cascade whereby poeciliids alter entire pond ecosystems by reducing the abundance and feeding of a single species, H. rubra . The relative lack of other species of invertebrate grazers in this system, and, specifically, the lack of any species resistant to poeciliid predation, prevents compensation by other members of the community from offsetting the effects of reduced H. rubra grazing.…”
Section: Discussionmentioning
confidence: 94%
“…Collectively, our findings suggest that negative effects of mosquitofish on native amphibians can be strong under certain settings, but they may also be influenced by factors such as community structure, habitat characteristics and productivity. Prior research has also shown that hydrological characteristics can mediate the effects of mosquitofish on some native species (Ho, Bond & Lake, ). Repeating our mosquitofish introduction within a less complex or productive habitat, and/or introducing mosquitofish earlier in the season, may have resulted in stronger effects on amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…Changes along environmental gradients can alter which taxa are present and their abundance (community composition) and the trophic interactions between taxa (food-web structure). By including all species present and their interactions, we can understand how whole ecosystems respond to stressors such as invasive species (Ho, Bond, & Lake, 2011), drought (Ledger, Brown, Edwards, Milner, & Woodward, 2013), or climate change (Binzer, Guill, Brose, & Rall, 2012). By including all species present and their interactions, we can understand how whole ecosystems respond to stressors such as invasive species (Ho, Bond, & Lake, 2011), drought (Ledger, Brown, Edwards, Milner, & Woodward, 2013), or climate change (Binzer, Guill, Brose, & Rall, 2012).…”
Section: Introductionmentioning
confidence: 99%